Effect of tebuthiuron and temperature increase related to climate change on the photosynthesis of Nitella microcarpa var. wrightii (Charophyceae) - Vilas Boas, Lucas Kortz [UNESP]; Branco, Ciro Cesar Zanini [UNESP] (Springer Nature, 2022)
The Charales is an important order of freshwater algae, closely related to embryophytes and relevant primary producer in the aquatic food web, capable of increasing water transparency and habitat heterogeneity. Anthropogenic activities such as use of herbicides in agricultural areas and the temperature increase related to climate change can combine into a multi-stressor environment and potentially influence the photosynthetic performance of such organisms. Using chlorophyll a fluorescence analysis we evaluated the photosynthesis of Nitella microcarpa var. wrightii after 7 days exposure to multi-stressor scenarios composed of different nominal concentrations of the herbicide tebuthiuron (0.05, 0.6 and 1.2 mg L−1) and two temperature increase scenarios related to projections by the Intergovernmental Panel on Climate Change (RCP 4.5 and RCP 8.5). The chlorophyll a fluorescence parameters were significantly different in the multi-stressor treatments. Very evident negative effects were found in treatments with nominal concentrations of 0.6 mg L−1 tebuthiuron or higher, with significant reductions in all measured fluorescence parameters. In addition, tests showed that while tebuthiuron by itself reduced the electron transport rate (ETR) of this species in all tested concentrations, the temperature increase in the RCP 8.5 scenario significantly strengthened the action of the herbicide. Our study highlights that unrestrained usage of pesticides such as tebuthiuron could not only jeopardize the physiological performance of N. microcarpa but also negatively influence their carbon fixation and contribution to primary productivity in aquatic ecosystems, especially in scenarios where the temperature increase due to climate change lessens the ability of these organisms to withstand other stressors.
Keywords: Charales; Chorophyll a Fluorescence; Herbicide; IPCC; Multi-stressor; Sugarcane Cultivation Scenario